2005
DOI: 10.1002/ccd.20521
|View full text |Cite
|
Sign up to set email alerts
|

Safety of adjunctive intracoronary thrombolytic therapy during complex percutaneous coronary intervention: Initial experience with intracoronary tenecteplase

Abstract: Intracoronary thrombus is associated with increased risk of in-laboratory vessel closure, recurrent myocardial infarction (MI), urgent vessel revascularization, and death. There is a lack of consensus on what represents the ideal treatment for patients with thrombotic complications during percutaneous coronary intervention (PCI), but the development of newer thrombolytic agents with increased fibrin specificity and longer half-life provides a potentially useful treatment option. In this study, the safety and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 16 publications
2
30
0
Order By: Relevance
“…Gurbel PA et al found that lesion-directed delivery of alteplase resulted in more prolonged local thrombolysis and thrombus score reduction in 45 unstable angina patients with coronary thrombus 10) . Recently, Kelly RV et al reported that the administration of intracoronary thrombolytics (tenecteplase) in complex PCI after the onset of thrombotic complications is safe and may even improve the success rate in PCI complicated by thrombus in the study of 34 patients (22 with acute ST elevation MI, 4 with rescue PCI, 6 with non-ST elevation MI, and 2 during elective PCI) 11) . Additionally Hara et al demonstrated in their report that the incidence of noreflow was lower and the angiographical success rate was higher for thrombolysis than angioplasty in acute myocardial infarction patients with thrombus-rich lesions 12) .…”
Section: A B Cmentioning
confidence: 99%
“…Gurbel PA et al found that lesion-directed delivery of alteplase resulted in more prolonged local thrombolysis and thrombus score reduction in 45 unstable angina patients with coronary thrombus 10) . Recently, Kelly RV et al reported that the administration of intracoronary thrombolytics (tenecteplase) in complex PCI after the onset of thrombotic complications is safe and may even improve the success rate in PCI complicated by thrombus in the study of 34 patients (22 with acute ST elevation MI, 4 with rescue PCI, 6 with non-ST elevation MI, and 2 during elective PCI) 11) . Additionally Hara et al demonstrated in their report that the incidence of noreflow was lower and the angiographical success rate was higher for thrombolysis than angioplasty in acute myocardial infarction patients with thrombus-rich lesions 12) .…”
Section: A B Cmentioning
confidence: 99%
“…In recent years, intracoronary thrombolysis has regained popularity as an adjuvant therapy for primary PCI, as studies using different thrombolytic agents and improved antiplatelet regimens showed it to be safe and effective. Kelly et al [12] reported that intracoronary infusion of tenecteplase was safe and effective for coronary flow recovery in patients with myocardial infarction. More recently, Boscarelli et al [13] found that adjuvant intracoronary infusion of low dose tenecteplase and alteplase in STEMI significantly reduced the thrombi remaining after MAT and improved coronary blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Kelly et al [71] demonstrated that TNK-supported PCI significantly improved the no reflow phenomenon in these patients. IC tPA was studied by Abbas et al in the setting of recanalization for chronic total occlusion among patients with progressive symptoms in whom prior attempts failed.…”
Section: Ic Thrombolyticsmentioning
confidence: 97%